Do Family and Institutional Ownerships Influence the Corporate Dividend Policy? - Santoso, Christheana; Salim, Richenda Feily; Pranoto, Titin; Adelina, Yang Elvi (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2021)
The difference of interests among shareholders in the middle of ownership structure that is dominated by majority shareholders enlarges the possibility of deprivation towards the minority shareholders' rights. Therefore, a dividend is considered as a tool to reduce conflict of interests between both parties with the assurance of pro-rata distribution of the company's resources. Family and institutional ownerships have unique characteristics that are frequently found in Indonesian firms. Thus, this study intended to analyze the impact of majority ownership owned by family and institution to dividend policy in nonfinancial firms listed in Bursa Efek Indonesia (BEI) during 2013-2017. The samples are chosen with the purposive sampling method resulting in 373 firms and 1.484 observations obtained. The data used in this study was secondary data from firms' annual and financial reports along with data extracted from Capital IQ. According to the regression results using the fixed-effect model, this study confirms the negative impact of majority ownership owned by families towards firms' dividend policy. Whilst, majority ownership owned by institutions shows that it has no significant impact on dividend policy. Otherwise, profitability, size, and leverages are proven to impact firms’ dividend policy. However, growth indicates no significant impact.